Manajemen Pembelajaran Tahfidz Al-Qur’an di Rumah Yatim dan Pesantren Ruhama Bogor - Amirul Mukmin; Nanat Fatah Natsir; Muhamad Faqihudin (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2020)
The problem of this research is the tahfidz Al-qur’an learning management model the purpose of this study is for orphans and ruhama Islamic boarding schools in bogor because in the orphans and Islamic school of ruhama memorized the holy qur’an The results of this study indicate that first, planning in Rumah Yatim and Pesantren Ruhama Bogor carried out activities (1) developing a strategic plan, which included vision and mission, objectives, strategic programs, implementation strategies, monitoring and evaluation; (2) arranging the rules of the santri (3) compiling technical guidelines for the implementation of activities. Second, organizing in managing Rumah Yatim and Pesantren Ruhama Bogor, including (1) arranging the organizational structure and the map of the program's responsibility (2) preparing the tasks and positions of each personnel (3) structuring the program. Third, the mobilization in Rumah Yatim and Pesantren Ruhama Bogor was said to be (1) motivating; (2) coordination; (3) leadership and (4) maintaining good relations with ustadh, santri and staff. Fourth, controlling in Rumah Yatim and Pesantren Ruhama Bogor is divided into (1) monitoring and evaluation (2) assessment. Fifth, the constraints of management of Islamic education institutions in the Islamic program in Rumah Yatim and Pesantren Ruhama Bogor consist of, (1) financial activities and operations in Rumah Yatim and Pesantren Ruhama Bogor still rely on permanent donors; (2) makeshift facilities; (3) Inadequate human resources. The six obstacles faced in the tahfiẓ al-Qur'an program are (1) the saturation and laziness felt by the santri in carrying out established programs; (2) guarding the memorization of the Qur'an that has been memorized (3) guarding themselves from immorality. This type of research is qualitative research, namely research that produces descriptive data, namely a type of research that seeks to present data and actual facts about the management of Islamic education institutions in the tahfiẓ al-Qur'an program in Ma'had Umar Bin Al-Khattab University Muhammadiyah Surabaya. Data collection techniques used in this study were (1) interview (2) observation (3) documentation. For data analysis using descriptive techniques, the application is carried out in three activities, namely data reduction, data presentation, and conclusion or verification. The results of this study indicate that (1). There are internal and external factors (2). The impact caused in the application tahfidz lerning management model memorizing the holy qur’an program that high enthusiasm and motivation in memorizing the holy qur’an (3). The need to develop a comparative management of Islamic education institutions in the holy qur’an program, specially the management of Islamic education institutions of Rumah Yatim and Pesantren Ruhama Bogor.